Axisymmetric PDMS (polydimethysiloxane) microchannels for in vitro haemodynamic studies - Lima, Rui A. (2009)
The current microdevices used for biomedical research are often manufactured using microelectromechanical systems (MEMS) technology. Although it is possible to fabricate precise and reproducible rectangular microchannels using soft lithography techniques, this kind of geometry may not reflect the actual physiology of the microcirculation. Here, we present a simple method to fabricate circular PDMS microchannels aiming to mimic in vivo microvascular environment and suitable for state-of-the-art microscale flow visualization techniques, such as confocal uPIV/PTV. By using a confocal uPTV system individual red blood cells (RBCs) were successfully tracked trough a 75 um circular PDMS microchannel. The results show that RBC lateral dispersion increases with the volume fraction of RBCs in the solution, i.e. with the hematocrit.